2005
DOI: 10.1016/j.apmr.2004.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Subject- and Injury-Related Factors Influencing the Course of Manual Wheelchair Skill Performance During Initial Inpatient Rehabilitation of Persons With Spinal Cord Injury

Abstract: ABSTRACT. Kilkens OJ, Dallmeijer AJ, Angenot E, Twisk JW, Post MW, van der Woude LH. Subject-and injury-related factors influencing the course of manual wheelchair skill performance during initial inpatient rehabilitation of persons with spinal cord injury. Arch Phys Med Rehabil 2005;86:2119-25.Objectives: To study changes in wheelchair skills in subjects with spinal cord injury (SCI) during rehabilitation; to determine whether changes in wheelchair skill performance are related to the subject, lesion characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
2
15
0
2
Order By: Relevance
“…These results are in line with other studies that identified personal characteristics (level of injury and age) as having an impact on the MWC skills of people with SCI. 9,19 Mean daily wheeled distance observed in the study participants is consistent with previous studies reported in the literature, 20,21 but with lower wheeled speed. Data were collected partly during the cold season (between October 2009 and June 2010), which could help explain this phenomenon.…”
Section: Discussionsupporting
confidence: 81%
“…These results are in line with other studies that identified personal characteristics (level of injury and age) as having an impact on the MWC skills of people with SCI. 9,19 Mean daily wheeled distance observed in the study participants is consistent with previous studies reported in the literature, 20,21 but with lower wheeled speed. Data were collected partly during the cold season (between October 2009 and June 2010), which could help explain this phenomenon.…”
Section: Discussionsupporting
confidence: 81%
“…According to Ronen et al, a prolonged stay in a specialized center may be positively associated with an improved rehabilitation outcome measured by the Spinal Cord Independence Measure [20]. Elsewhere, we reported improvement of wheelchair skills after the first 3 months of functional rehabilitation [30], a period that is longer than the mean total period of inpatient rehabilitation in several countries [4,[16][17]. However, discharge also may be delayed because people have to wait for completion of domestic adaptations or delivery of assistive devices.…”
Section: Length Of Stay and Outcomesupporting
confidence: 50%
“…Therefore, as the current study utilized field tests, it is probable that the skills required to perform these, such as turning and backward pulling, were more complex and required more time to learn [25,26].…”
Section: Discussionmentioning
confidence: 98%